2019
DOI: 10.1002/biof.1566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin on mitochondria in neurodegenerative diseases

Abstract: This article may be used for non-commercial purposes in accordance With Wiley Terms and Conditions for self-archiving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(55 citation statements)
references
References 144 publications
0
51
0
1
Order By: Relevance
“…As pio, curcumin induces cell differentiation and protection from TNF-γ damage through activation of the PPAR-γ pathway in OPs [ 38 ]. On the other hand, curcumin induces phase II enzymes and protects from oxidative and mitochondrial stress by activating NRF2 in different cell types [ 57 , 58 ]. In this study, we demonstrate that, in OPs, the effect of curcumin on mMP is similar to the DMF effect, suggesting an electrophile-type effect.…”
Section: Discussionmentioning
confidence: 99%
“…As pio, curcumin induces cell differentiation and protection from TNF-γ damage through activation of the PPAR-γ pathway in OPs [ 38 ]. On the other hand, curcumin induces phase II enzymes and protects from oxidative and mitochondrial stress by activating NRF2 in different cell types [ 57 , 58 ]. In this study, we demonstrate that, in OPs, the effect of curcumin on mMP is similar to the DMF effect, suggesting an electrophile-type effect.…”
Section: Discussionmentioning
confidence: 99%
“…107 Encouragingly, it has been reported that curcumin could protect mitochondria from oxidative damage through reducing the intracellular generation of ROS and synchronously alleviating the apoptosis of cortical neurons in rats. 108 Besides, curcumin can also ameliorate the aflatoxin B-induced apoptosis through the mitochondrial pathway in liver cells. 109 Furthermore, curcumin can not only mediate neuroprotection against mitochondrial complex I and II inhibitors by activating the nuclear factor erythroid 2-related factor 2 (Nrf2), but also mitigate the mitochondrial dysfunction by suppressing the ROS burst and the enhancing mitochondrial antioxidant gene expression.…”
Section: Mitochondrial Function-related Antidepressant Mechanismsmentioning
confidence: 99%
“…Curcumin, a curcuminoid [ 1 ], is a bioactive component representing 1.5–3 wt.% [ 2 ] of the rhizome of turmeric ( Curcuma longa ) [ 3 ], also known as diferuloylmethane. This yellow pigmented powder can be obtained by grinding the rhizome of turmeric [ 4 ], owing the color to the curcumin present [ 1 , 5 ]. It has been used over the centuries for cooking, especially in Asia, as well as for treatment due to its curing properties in diseases, such as dysentery, chest congestion, and pain.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past half a century, curcumin has received growing interest in biological [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], pharmacological [ 15 , 16 , 17 , 18 , 19 ], and nutraceutical research [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Interestingly, it was in 1949 that its antibacterial properties were discovered [ 1 ]. Since then, many studies have proved that curcumin also possesses other potential beneficial properties, such as anti-inflammatory [ 27 , 28 ], antiproliferative [ 29 , 30 ], antimetastatic [ 31 , 32 ], anti-angiogenic [ 29 , 33 ], antidiabetic [ 34 , 35 , 36 ], hepatoprotective [ 37 , 38 , 39 ], anti-atherosclerotic [ 40 , 41 ], antithrombotic [ 42 ], wound healing [ 43 ], anti-cancer [ 44 ], anti-arthritic [ 45 ], neuroprotective [ 46 , 47 ], analgesic [ 45 ], immunomodulatory [ 48 , 49 , 50 , 51 ], and pulmonoprotective […”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation